Effect of human urine as fertilizer on crop production - Upreti, HK; Shrestha, P; Paudel, P (Agronomy Journal of Nepal, 2013)
Nutrient cycling in the soil-plant ecosystem is an essential component of sustainable agriculture. Human excreta though have high nutrient value is being neglected and simply dumped as waste. Out of the human excreta, urine has high nitrogenous fertilizer value than feces. Hence by separating urine in ECOSAN toilet, it can be of great use in fulfilling the fertilizer demand of the country. The main objective of this study is to assess the effect of human urine on crop yield and to find out the appropriate urine dose and time of application to different crops. The study shows that urine can act as effective as a chemical fertilizer and can be used as an efficient source of plant nutrients. In general, 2-3 splits urine application in addition with phosphorus and potash fertilizer gave the comparable result with that of chemical fertilizer. Though there is no statistical difference in production of the crops, the average yield was found to be higher in the application of chemical fertilizer in all crops except in wheat. From the study, it can be concluded that any crops can be grown using urine as a fertilizer without significant reduction in the yield if nutrient losses during handling could minimize. The study recommends the further study in a long-term urine application trial to verify the obtained result and also to observe the effect of urine on soil properties and plant health as well as on the efficacy of urine along with compost in crop production. DOI: http://dx.doi.org/10.3126/ajn.v2i0.7532 Agronomy Journal of Nepal (Agron JN) Vol. 2: 2011 pp.168-172